Egyptian foreign policy under Mohamed Morsi: Domestic considerations and economic constraints - Stephan Roll; Jannis Grimm (Stiftung Wissenschaft und Politik (SWP), 2012)
Since taking office, President Mohamed Morsi has clearly set himself apart from his predecessor Hosni Mubarak, as reflected in two trends: asserting a regional leadership role for Egypt and opening Cairo's foreign policy to new potential partners. But although Morsi comes from the Islamist Muslim Brotherhood, his foreign policy is not one of fundamental ideological reorientation. Instead, he seeks to boost popular support through foreign policy activism and thus compensate for lack of success in economic and social policy. However, given the lack of possibilities to exert influence, Egypt is in little position to fill out a regional leadership role. And in view of the difficult economic situation neither the President nor the Muslim Brotherhood leadership backing him have any interest in alienating Egypt's traditional partners
Keywords: 320